PENGARUH LUAS PANEN DAN PRODUKSI PADI TERHADAP KETERSEDIAAN BERAS DI KABUPATEN MUARA ENIM - firda novalia; Putri ogari (JASEP, 2022)
The problem that accurs is that Muara Enim Regency Is not a food insecure area so that the availability of rice in Muara Enim Regency is low. This study aims to determine how to effect harvested area and rice production on rice availability in Muara Enim Regency. The research method used quantitative research and method of analysis used is multiple linear regression. While the data Collecteed came from 20 sub-districts in Muara Enim for period of 6 years (2013-2018). The result showed that overall harvested area and rice production had significant effect while partially harvested area and rice production had a significant and positive effect on rice availability in Muara Enim Regency.Keywords : availability, harvested area, production